SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KARYAWAN TERBAIK DENGAN ADAPTASI PROFILE MATCHING - Ruth Silvia Damaiyanty; Agustina Verawati Silitonga; Irwansyah Irwansyah; Michael Michael (STMIK Widuri Jakarta, 2024)
PT. XYZ which has been established since 1989, this company provides an educational curriculum and system integrator starting from kindergarten, elementary, junior high to high school/vocational school. Pt.xyz already has a long experience and is also a loyal customer for modern Information & Communication Technology (ICT) curriculum products in private schools in the areas of Medan, Lampung, Central Java, East Java to Jabodetabek. Currently there is a problem in processing employee data, especially for the employee performance appraisal process. There is a time limit for accessing the Key Performance Indicators (KPI) system every month, when the period ends each October it will be difficult to see the history of the assessment. The purpose of this study is to produce a web-based decision support system for determining the best employees that can help provide alternative choices for PT. XYZ in making decisions. The method used in this study is the Profile Matching method to provide recommendations in the form of the best employees based on rank. Ratings are intended for employees who are entitled to a promotion or bonus. The results of testing the decision support system itself used the User Acceptance Test (UAT) where the results of the decision support system respondents got an average value of 82% where the value was in the good category.